2018
DOI: 10.24099/vet.arhiv.0229
|View full text |Cite
|
Sign up to set email alerts
|

In vitro and in vivo assessment of orf virus (ORFV) by electron microscopy

Abstract: Transmission electron microscopy (TEM) was employed for describing skin and scab lesions in goats affected by orf virus and to demonstrate the parapoxvirus from clinical suspensions by negative staining and ORFV confirmation by immunogold electron microscopy. All samples were confirmed as parapoxvirus by semi-nested PCR amplification of partial gene encoding for the B2L envelope protein. Skin lesions were characterized by ballooning degeneration and loss of desmosomes of the spinosum cells, cytolysis and vesic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 21 publications
(28 reference statements)
0
8
0
Order By: Relevance
“…26 This pattern wrapping around the particle surface is genetically encoded in the virus genome. [26][27][28] The mature ORFV particle when emerged from an infected cell after lysis appears enveloped and infectious. However, when the virions are viewed intracellularly, some of the particles appeared to possess a second wrapping membrane that originates from the Golgi apparatus and buds off the infected cell as external enveloped virion.…”
Section: Orf Virus Structurementioning
confidence: 99%
See 3 more Smart Citations
“…26 This pattern wrapping around the particle surface is genetically encoded in the virus genome. [26][27][28] The mature ORFV particle when emerged from an infected cell after lysis appears enveloped and infectious. However, when the virions are viewed intracellularly, some of the particles appeared to possess a second wrapping membrane that originates from the Golgi apparatus and buds off the infected cell as external enveloped virion.…”
Section: Orf Virus Structurementioning
confidence: 99%
“…82 ORFV observed under electron microscopy demonstrates a classic ovoid crisscrossed viral particle that helps for differential diagnosis (Figure 1). 27 On the other hand, ORFV isolation using different tissue culture systems and embryonated eggs are potential options; however, the growth rate of ORFV can be slow and variable. 81 Moreover, isolation of the virus in tissue culture usually requires primary cell lines that are relatively difficult to obtain on a routine basis compared to continuous cell culture systems for the developing world.- 83 The cell culture system is normally employed in a live attenuated ORFV vaccine preparation for animals such as primary neonatal bovine or ovine testicular cells used to culture the virus.…”
Section: Usa Laboratory Diagnosismentioning
confidence: 99%
See 2 more Smart Citations
“…Besides the current applications, other confirmatory applications were also employed. In our earlier studies, ORFV has also been successfully cultured in continuous lamb testis cells (OA3.Ts) (Nashiruddullah et al, 2016) and the virus has been demonstrated by immunofluorescence and visualized by Transmission Electron Microscopy (TEM) (Nashiruddullah et al, 2018). ELISA applications for antibody detection showed positive results and were consistent.…”
Section: Dot-elisa For Antibody Detectionmentioning
confidence: 89%